2009
DOI: 10.1007/s10865-009-9236-1
|View full text |Cite
|
Sign up to set email alerts
|

Type D personality is a predictor of poor emotional quality of life in primary care heart failure patients independent of depressive symptoms and New York Heart Association functional class

Abstract: Quality of life is an important patient-centered outcome and predictor of mortality in heart failure, but little is known about the role of personality as a determinant of quality of life in this patient group. We examined the influence of Type D personality (i.e., increased negative emotions paired with emotional non-expression) on quality of life in primary care heart failure patients, using a prospective study design. Heart failure patients (n = 251) recruited from 44 primary care practices in Germany compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 45 publications
3
33
0
8
Order By: Relevance
“…Impaired HRQOL has also been observed both in Type-D coronary artery bypass grafting surgery patients [24] and in a sample of Type-D coronary artery disease patients both pre-and post-cardiacrehabilitation as compared to non-Type-D patients [25]. Impaired emotional HRQOL is also associated with Type-D personality in primary care heart failure patients [26] Biochemical markers Biological indicators of prognosis in cardiovascular disease include proinflammatory cytokines. Two important proinflammatory cytokines are tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6).…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Impaired HRQOL has also been observed both in Type-D coronary artery bypass grafting surgery patients [24] and in a sample of Type-D coronary artery disease patients both pre-and post-cardiacrehabilitation as compared to non-Type-D patients [25]. Impaired emotional HRQOL is also associated with Type-D personality in primary care heart failure patients [26] Biochemical markers Biological indicators of prognosis in cardiovascular disease include proinflammatory cytokines. Two important proinflammatory cytokines are tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Relevant titles were identified, and their abstracts were reviewed for possible inclusion. One additional study [26] was serendipitously identified as a result of editorial work by K.S.M. During the review process, two additional studies that reviewers suggested and that met inclusion criteria were added [40,41].…”
Section: Study Search Proceduresmentioning
confidence: 99%
“…A large body of evidence has suggested a link between Type D and subjective health (including impaired physical health, increased symptoms of depression and anxiety, and lower quality of life) in CHF patients and those with peripheral arterial disease (PAD) [18][19][20][21][22]. Studies have also demonstrated the usefulness of the Type D construct in predicting subjective outcomes in post-MI patients.…”
Section: Introductionmentioning
confidence: 99%
“…B. Angst oder bestimmte Persönlichkeitszüge [27]. Auch die bei herzinsuffizienten Patienten häufigen sexuellen Funktionsstörun-gen können zur psychischen Belastung und zur Einschränkung der Lebensqualität führen [28].…”
Section: Introductionunclassified